The Role of Forensic Medicine in Disclosing Premediated Killers (Study of Decision No. 116/Pid.B/2019/PN.Bms) - Aulia Ineke Fitri (Faculty of Law Universitas Muhammadiyah Purwokerto, 2020)
Forensic medical science is a science that is used for legal purposes by providing scientific evidence that can be used in solving crimes, especially the crime of murder. This science studies the cause of death, identification, state of post-mortem corpses. This study will discuss the role of forensic medicine in uncovering the crime of premeditated murder in case no. 116/Pid.B/2019/PN.Bms. The research method used is normative juridical, which is carried out through a literature study that examines secondary data in legislation and other legal documents, research results, assessment results, other references and is equipped with interviews. This study concludes that forensic medicine plays an essential role in investigating the crime of premeditated murder in case no. 116/Pid.B/2019/PN.Bms because of the need to identify corpses that have become bones and charred, so how important it is that forensic medicine is poured into evidence in the letter category in the form of Visum et Repertum, which by police investigators is under Article 133 of the Criminal Procedure Code to be used as legal evidence in uncovering and seeking the material truth of a criminal act that occurred. Suggestions in this study include providing education to the public regarding the treatment of evidence and the crime scene to change the disclosure of cases. Keywords: Classification, Inheritance Certificate, Discrimination